Pengembangan Media Pembelajaran Berbasis Android Menggunakan Smart Apps Creator Pada Materi Bangun Ruang Sisi Datar di Kelas VIII SMP Negeri 2 Amabi Oefeto - Hello, Risky Arnis Septian (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to develop android-based mathematics learning media using Smart Apps Creator on flat-sided space building material for class VIII students of SMP Negeri 2 Amabi Oefeto which is valid, practical, and effective. The method used in this research is the Research and Development method with the ADDIE model, namely: analysis, design, development, implementation, and evaluation. The data collection techniques and instruments used were interviews, questionnaires, and tests. The results showed that the average validity of the media was 4.5 including the "very valid" category. For the practicality aspect, the average teacher response result is 4.56, the response from small class students is 4.6 and the large class is 4.8 so that it is included in the "very practical" category. For the effectiveness criteria, the percentage of small class learning completeness is 100% and the large class obtained 71.8% completeness so that it is categorized as "effective". Thus, the learning media developed is valid, practical, and effective